Pseudomonas nosocomialis sp. nov., isolated from clinical specimens. Issue 11 (2nd August 2019) - Mulet, Magdalena; Gomila, Margarita; Ramírez, Antonio; Lalucat, Jorge; Garcia-Valdes, Elena
Abstract : Strains A31/70 T, CCUG 58779 and SD129 were Gram-stain-negative, short rods, motile by one polar flagellum and isolated from clinical specimens in Botswana, Sweden and Spain, respectively. The 16S rRNA sequence similarity values grouped them in the Pseudomonas stutzeri phylogenetic group of species. The DNA G+C content ranged from 65.5 to 65.7 mol%. The strains were characterized phenotypically by the API 20NE and Biolog GEN III tests, and chemotaxonomically by their whole-cell MALDI-TOF MS protein profiles and by their fatty acid contents. The absence of the arginine dihydrolase and the hydrolysis of gelatin differentiated these strains from the closest species, Pseudomonas azotifigens . The major fatty acid contents were summed feature 8 (38.6 %), C16 : 0 (22.6 %), summed feature 3 (20.5 %) and C12 : 0 (8.4 %). Multilocus sequence analysis with three housekeeping gene sequences ( rpoD, gyrB and 16S rRNA) together with whole-genome comparisons indicated that these strains cluster together in the phylogenetic analysis and their similarity values were lower than the thresholds established for species in the genus Pseudomonas . These results permit us to conclude that strains A31/70 T, CCUG 58779 and SD129 belong to a novel species in the genus Pseudomonas for which the name Pseudomonas nosocomialis sp. nov. is proposed. The type strain is A31/70 T (=CECT 9981 T =CCUG 73638 T ).